RESPONSE OF SOME COWPEA VARIETIES (Vigna unguiculata L.) YIELD TO VARIATIONS IN DAYLENGTH IN SUDAN SAVANNA OF NIGERIA - Nuhu, Y.; Mukhtar, F. B.; Mohammed, I. B.; Aliyu, B. S.; Namadina, M. (FUDMA JOURNAL OF SCIENCES, 2023)
Photoperiodism is the effect of day length on plant growth and development particularly in the control of flowering; it is the response of organisms to the timing of light and darkness. Also defined as the use of day length to measure the time or year and to regulate physiological processes. This study was carried out to determine the response of some cowpea varieties yield to variations in day lengths. Nine cowpea cultivars were used in the study. The varieties were (IT99K-241-2, IT97K-568-19, IT99K-1092-2, IT97K-454-3, IT99K-216 -48-1, IT99K-213-11-1, IT97K-409-4, IT98K-131-2 and IT93K-452-1). Yield of the cowpea varieties were studied under different day length conditions i.e. natural, short and extended day lengths. A Screen house was used for the natural day length, the dark room represented the short day length and light illumination area represented the long day length periods. The varieties were planted in March, 2008 for the dry season and in July for the rainy season 2008. Analysis of variance was carried out to determine the effects of Day lengths on yield.  In the rainy season (2008) the highest yield in terms of number of pods was obtained in variety IT97K-568-19 while the highest yield in terms of number of seeds per pod was obtained in the variety IT99K-213-11-1. The least yield was obtained in variety IT99K-241-2. In the dry season, (2008) however, the highest yield in terms of number of pod was obtained in the variety IT97K-409-4 while the highest yield in terms of number of seeds per pod